SWOT ANALYSIS OF HYDROGEN ECONOMY (ETIMA, 2024)
The paper deals with the types of hydrogen production, methods for its storage and transport, and possibilities of end use of hydrogen. The basics of the hydrogen economy are briefly described and then the SWOT analysis of the hydrogen economy is performed. The strengths, weaknesses, opportunities, and threats of the hydrogen economy are summarized in the SWOT analysis. Based on that analysis, the biggest problems, and threats with possibilities of solving those problems are summarized. SWOT analysis considers aspects of the hydrogen economy e.g. energy demands, financial difficulty, safety, and awareness about hydrogen. Conclusions involve suggestions on how to avoid the above-mentioned awareness, and how could increase hydrogen utilization.